The effect of continuous feeding of gliricidia on reproduction and production performances of Javanese Fat-Tailed sheep: Impact on the second breeding - Supriyati .; I-G.M Budiarsana; I-K Sutama (Jurnal Ilmu Ternak dan Veteriner, 1999)
The effect of continuous feeding of gliricidia on reproduction and production performances in second breeding of Javanese Fat-Tailed (JFT) sheep through the second breeding period was studied. Twenty six ewes post lactation at first lambing (body weight 22.5-26.5 kg) were divided into four treatment groups. Each group consisted of 6 animals except Group D had 8 animals. They were given King grass (Pennisetum purpureophoides) and gliricidia (Gliricidia sepium Jacq.) leaf with ratio of 100:0 (Group A = control), 75:25 (Group B), 50:50 (Group C) and 0:100 (Group D). Forages were given 2.5-3% (dry matter) of liveweight. All groups were supplemented with 100g/head/day concentrate (crude protein = 16%), but during late pregnancy and lactation they were supplemented at 200 g/head/day. Results showed that feeding gliricidia 25-100% of total forages improved body weight due to the increasing protein intake. The maximum concentration of progesteron increased from 0.81 to 2.78 ng/ml. The ovulation rate and prolification also increased significantly (P<0.05) from 1.6 to 3.0 and 1.33 to 2.38, respectively. Individual birth and weaning weights of the lambs were not affected. It is concluded that feeding gliricidia continuously up to 100% as forages and supplemented with concentrate gives positive effect on bodyweight gain, reproduction and production performances in second breeding of JFT sheep.   Key words : Sheep, gliricidia, reproduction, second breeding